3(5-2x)+22=2x-2(4-x)

Simple and best practice solution for 3(5-2x)+22=2x-2(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5-2x)+22=2x-2(4-x) equation:



3(5-2x)+22=2x-2(4-x)
We move all terms to the left:
3(5-2x)+22-(2x-2(4-x))=0
We add all the numbers together, and all the variables
3(-2x+5)-(2x-2(-1x+4))+22=0
We multiply parentheses
-6x-(2x-2(-1x+4))+15+22=0
We calculate terms in parentheses: -(2x-2(-1x+4)), so:
2x-2(-1x+4)
We multiply parentheses
2x+2x-8
We add all the numbers together, and all the variables
4x-8
Back to the equation:
-(4x-8)
We add all the numbers together, and all the variables
-6x-(4x-8)+37=0
We get rid of parentheses
-6x-4x+8+37=0
We add all the numbers together, and all the variables
-10x+45=0
We move all terms containing x to the left, all other terms to the right
-10x=-45
x=-45/-10
x=4+1/2

See similar equations:

| c-42=17 | | 5(x-5)=2x+11 | | 5z-18=57 | | 11(4x-3)=22(2x-3 | | 7v=140 | | 10-⅔x=8 | | r−17.7=−6.2 | | 24.5=t-7.2 | | 1x+4|=7 | | x−17.7=−6.2 | | 3x2–28x–55=0 | | (11+2y)5-7y=-13 | | (x-3)^3=729 | | -8(-7+8b)+3=-136 | | m/(-3)=(-7) | | 5.2+x=-8 | | 177147=3^n-1 | | y*2=81 | | 4x+5=-1x=3 | | 177147=3n-1 | | 4d2+14d+12=0 | | 0.11(x+2,000)=4,510 | | x-588=1,346 | | 3x+12=-12+5x | | 4m2+12m=0 | | -4n^2-8n-3=-3-5n^2 | | -4x+28=100 | | 3/2-e=3/8 | | 5x+5-x=53 | | 3x2+19x-14=0 | | 180-x=280-3x | | 2(7x-3)=4(7-2x)+5x |

Equations solver categories